The relationship between the King al-Kamil of Ayyubid and Emperor Frederick II )H /1226-1229 AD-624-626( - حسن غادة; بايرلي منال (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The Relations between the European West and the Arab-Islamic East on the eve of the Sixth Crusade witnessed a major diplomatic activity, especially between the King al-Kamil of Ayyubid and the German Emperor Fredrick II. Several factors have come together to establish these relations, the most important of which is the disagreement between the pontifical and the German emperor who arrived in Acre in 626 Ah/1228. In addition, the political situation in the Levant and Egypt was disrupted by the conflict between the members of the Ayyubid House to dominate the entire country, and their use of external forces against each other.